Qualidade De Produtos De Origem Animal 2 2019
DOI: 10.22533/at.ed.66619121118
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência De Parasitas Humanos E Elementos Exógenos Em Alfaces Cultivadas Na Região De Inhumas – Goiás

Abstract: Todo o conteúdo deste livro está licenciado sob uma Licença de Atribuição Creative Commons. Atribuição 4.0 Internacional (CC BY 4.0).O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores. Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possibilidade de alterá-la de nenhuma forma ou utilizá-la para fins comerciais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…were also not considered in the analysis. This is the highest percentage of lettuce contamination by parasites ever described in the state of Goiás (Neres et al, 2011;Gomes et al, 2014;Moura et al, 2016;Blanco et al, 2019), and similar or higher percentages have been reported in other cities mainly in the north and northeast of Brazil (Furtado et al, 2015;Novacki et al 2016;Pinto et el., 2018;Carvalho et al, 2019;Oliveira et al, 2020;Rodrigues et al 2020). The high prevalence in cities of these regions may be related to the lower percentages of basic sanitation, with emphasis on the sewage network, as described by Ministry of Cities in the National Plan for Basic Sanitation of 2019 (Brasil, 2019) and by Dantas et al (2012).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…were also not considered in the analysis. This is the highest percentage of lettuce contamination by parasites ever described in the state of Goiás (Neres et al, 2011;Gomes et al, 2014;Moura et al, 2016;Blanco et al, 2019), and similar or higher percentages have been reported in other cities mainly in the north and northeast of Brazil (Furtado et al, 2015;Novacki et al 2016;Pinto et el., 2018;Carvalho et al, 2019;Oliveira et al, 2020;Rodrigues et al 2020). The high prevalence in cities of these regions may be related to the lower percentages of basic sanitation, with emphasis on the sewage network, as described by Ministry of Cities in the National Plan for Basic Sanitation of 2019 (Brasil, 2019) and by Dantas et al (2012).…”
Section: Discussionsupporting
confidence: 51%
“…Parasitological evaluations of lettuce and collard green were conducted in the city of Anápolis, and in both surveys the contamination with parasitic protozoa and helminths was demonstrated (Neres et al, 2011;Moura et al, 2016). Gomes et al (2014) also detected enteroparasites in lettuce grown on the edge of the Cascavél river in Goiânia, and Blanco et al (2019) on lettuce produced and sold in the city of Inhumas. In Aparecida de Goiânia, second city in number of inhabitants of the State with almost 600,000 residents according to IBGE (2019), there is no record of parasitological analysis of foliar vegetables.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation